Marketing Philosophies and Market Orientation: A review and conceptual analysis - Molochny, Boris (Marketing & Menedzsment, 2019)
Why some companies are more successful than another? The answer probably depends by organizations ability to provide and deliver superior customer value. Marketing concept and market orientation are the aspects of business culture that motivates employees throughout the organization to place the highest priority on the profitable creation and maintenance of superior customer value.